THE EFFECT OF ENHANCED EXTENSIVE READING TO THE INCIDENTAL ENGLISH PREPOSITION ACQUISITION - Xenia, Tia; Anjani, Christiana Dwi Prisilia (LLT Journal: A Journal on Language and Language Teaching, 2022)
The English prepositions are still problematic for EFL learners since the existing knowledge of their first language hinders them from understanding the use of English prepositions. This study investigated the effect of enhanced extensive reading on their incidental English preposition acquisition. A total of 16 Indonesian University learners of English as a foreign language participated in this study. The treatment lasted for four weeks, initiated with the pretest. Two weeks after the treatment, the posttest was administered, followed by distributing questionnaires to find out the factors influencing them in doing the posttest. The results showed a significant improvement in the students' incidental acquisition of the targeted English prepositions after they received repeated exposure to the English prepositions through enhanced extensive reading. The factors influencing the improvement of their incidental acquisition involve their existing knowledge of the English prepositions and their built intuition in decision making. It is hoped that teachers and educational institutions are encouraged to add extensive reading to their curriculum.